Chapter La deissi personale e spaziale nelle epigrafi glagolitiche dell'Istria e della Dalmazia - MANZELLI, GIANGUIDO (Biblioteca di Studi Slavistici, 2016)
This paper deals with person and spatial deixis in the Glagolitic epigraphs of Istria and Dalmatia collected by Branko Fučić (1920-1999). The focus is mainly on spatial deixis offering interesting insights as far as the evolution of the Chakavian variety of Croatian across the past centuries is concerned. A statistical survey shows a significant difference between the old forms and the deictic system of modern Croatian. This kind of evolutionary development in the Croatian deictic system can be explained in terms of a semantic shift due to the obsolescence of the original proximal deictic se.